Optimization of Career Development Through the Transformation of Administrative Position into Functional Position in Makassar City - Kardiat, Yosar; Ibrahim, Muh Akmal; Ahmad, Badu; Susanti, Gita (Universitas Negeri Makassar, 2024)
The transfer of positions from administrative positions to functional ones is one of the ways to optimize the career development. policy for transferring positions was carried out without going through good preparation since it was established or at the time of its implementation. This study aims to analyze the optimization of career development through the transformation of administrative position into functional position in Makassar City. This study used a qualitative research method with the type of descriptive research. The data was collected through observation, in-depth interviews, and documentation. Data analysis techniques were carried out by data collection, data condensation, data display, and conclusions drawing/ verifying. The results show that in transformation position from administrative into functional can optimized the career development.